2009
DOI: 10.1136/hrt.2009.172569
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial deformation in aortic valve stenosis: relation to left ventricular geometry

Abstract: ObjectiveTo assess left ventricular (LV) strain and displacement and their relations to LV geometry in patients with aortic stenosis (AS).DesignCross-sectional echocardiographic study in patients with AS. Peak circumferential, radial and longitudinal strain, and radial, longitudinal and transverse displacement were measured by 2D speckle tracking. Severity of AS was assessed from energy loss index (ELI). LV hypertrophy was present if LV mass/height2.7 ≥46.7/49.2 g/m2.7 in women/men and concentric LV geometry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 34 publications
12
79
2
2
Order By: Relevance
“…Younan et al [18] showed a negative correlation of GLS with LVMI. Similar results were obtained by Cramariuc et al [19]. In the study by Dinh et al [20] GLS correlated with a degree of LV hypertrophy assessed by magnetic resonance imaging and was significantly worse in groups of patients with a greater degree of hypertrophy.…”
Section: Discussionsupporting
confidence: 78%
“…Younan et al [18] showed a negative correlation of GLS with LVMI. Similar results were obtained by Cramariuc et al [19]. In the study by Dinh et al [20] GLS correlated with a degree of LV hypertrophy assessed by magnetic resonance imaging and was significantly worse in groups of patients with a greater degree of hypertrophy.…”
Section: Discussionsupporting
confidence: 78%
“…[16][17][18] Furthermore, these parameters have been shown to be superior to LVEF to predict adverse outcomes in AS. [16][17][18][19][20] From a pathophysiological standpoint, these data are consistent with the concept that the increase in wall stress and intra-myocardial pressure as well as the reduction in M A N U S C R I P T…”
Section: Amount and Distribution Of Adiposity Versus LV Systolic Dysfsupporting
confidence: 75%
“…Several studies have demonstrated that GLS $215% should be considered pathologic (21)(22)(23). Therefore, we defined the cutoff point of GLS as 215%.…”
Section: Evaluation Of Cardiac Functionsmentioning
confidence: 99%